In-silico analysis of tenidap and its derivative as a novel 5-lipoxygenase inhibitor - Asma Noor; Ardas Masood; Jawaria Khan; Tanveer Abbas; Muhammad Imran Qadir (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2017)
Tenidap is a derivative of Flavonoids which are actually plant derivatives, it shows inhibition activity of 5-lipoxygenase. Molecular models were directed to discover molecular docking mode, also to help explain molecular tool behind its inhibitory action. Molecular relations of tenidap with the catalytic trio (His523, His518, Ile875) inside active or dynamic position of 5-lipoxygenase through hydrogen bonding, appears to the major reason elaborate in its substantial 5-lipoxygenase activity of inhibition.